Pedagogical beliefs of student teachers and school-based mentor teachers in the kurikulum merdeka context - Maida Azra Widowati; Iris Athamaica Lopez Palacios (UHAMKA Press, 2025)
Purpose: This study evaluates pedagogical belief disparities between PPG Prajabatan student teachers and school-based mentor teachers regarding cognitive goals (mechanical acquisition vs. higher-order reasoning) and social goals (compliance vs. agency) under Indonesia's Kurikulum Merdeka. Method: Utilizing a quantitative comparative cross-sectional survey design, data were collected from participants ( candidate-mentor dyads) across clinical placement sites using the validated Pedagogical Beliefs Inventory for Kurikulum Merdeka. Data were analyzed using independent-samples -tests and two-way MANOVA. Findings: Student teachers exhibited significantly higher endorsement for higher-order reasoning and social agency compared to mentors (). Conversely, school-based mentors prioritized mechanical acquisition and behavioral compliance. Mentoring tenure significantly moderated mentor mindsets (), with veteran mentors (>5 years) demonstrating high alignment with student-centered reform principles. Practical implications: Teacher Training Institutions (LPTKs) and educational policymakers must institute structured mentor training frameworks to harmonize academic coursework with clinical placements, ensuring sustainable student-centered instruction. Originality/value: This investigation provides unique empirical evidence by adapting sociocultural belief frameworks to an active national curriculum overhaul within a Global South teacher education setting.